The Endometrial Immune Profiling May Positively Affect the Management of Recurrent Pregnancy Loss - Cheloufi, Meryam; Kazhalawi, Alaa; Pinton, Anne; Rahmati, Mona; Chevrier, Lucie; Prat-ellenberg, Laura; Michel, Anne-Sophie; Dray, Geraldine; Mekinian, Arsène; Kayem, Gilles; Lédée, Nathalie (Frontiers in Immunology, 2021)
The endometrial immune profiling is an innovative approach based on the analysis of the local immune reaction of the endometrium at the time of the implantation. documenting the local immune activation during the period of uterine receptivity, aimed to detect and correct potential imbalances before and at the very beginning of placentation. The main objective of the study was to analyze in women with a history of repeated pregnancy loss (RPL) the association of personalized strategies based on immune deregulations with live birth rates. The secondary objective was to highlight the prognostic factors for live births. An observational retrospective analysis of a series of 104 RPL patients were included between January 2012 and December 2019. Inclusion criteria was a spontaneous fertility with at least three miscarriages, a complete check-up including a three-dimension Ultrasound, an endometrial biopsy for uterine immune profiling and a follow-up over at least 6 months with personalized care if indicated after the complete check-up. We defined as a success if the patients had a live birth after the suggested plan, as a failure if the patient did not get pregnant or experienced a new miscarriage after the targeted therapies. Uterine immune profiling was the only exploration to be significantly associated with a higher Live Birth Rate (LBR) if a dysregulation was identified and treated accordingly. An absence of local deregulation was associated with a higher risk of a new miscarriage suggesting that the cause inducing RPL still need to be identified. Independently of age and AMH level, deregulated immune profile is significatively associated with 3 times more live births than non-deregulated or five times if overactivated and treated by immunotherapy profile. The usage of ART was significantly associated with lower LBR regardless of the presence of a subfertility factor (p=0.012). Personalization of medical care using natural cycle or simple hormonal stimulation is associated with a higher LBR than personalization including ART treatments regardless of maternal age and AMH level. Our study suggests that some endometrial immune profiles with targeted management of RPL are associated with a higher rate of LBR. ART may be negatively associated with LBR.